PKM Ibu-Ibu PKK Desa Palaes Minahasa Utara Untuk Pemanfaatan Daun atau Bunga Mangrove sebagai Minuman Fungsional - Dingse Pandiangan; Nelson Nainggolan; Elvina Artha Nainggolan; Yultrina Taghulihi; Verina Putri Gloria Nainggolan; Eko Suyoko (JPAI: Jurnal Perempuan dan Anak Indonesia, 2022)
Palaes Village has a PKK Village management organization which consists of women or the wives of village administrators. Empowerment of the wives of village administrators and PKK is very necessary and urgent in supporting the development of Palaes Village to become a holistic Tourism Village Pilot Village. As a supporting tool and preparation towards this goal, women's empowerment is very much needed. This women's empowerment program is carried out in stages. In 2022, the introduction of mangrove plants, especially the flowers, is very attractive to be used as a functional tea. The steps and processes are carried out in stages and will be delivered in the socialization stage. The problem of Palaes Village in achieving this goal is that there are lots of mangrove leaves and litter there that often pollute and disturb the beauty if allowed to fall. Therefore, use flowers or leaves that have fallen to be used as functional tea drinks so that the wives and women of Palaes Village have work and creativity to be used as a means of developing tourism in their village later in the following year. Standardized product quality needs a good process so that the content of antioxidants and other important substances is good and the storage period is good. The stages that will be carried out are conveyed at the stage of socialization and introduction of the benefits of mangrove plants in this activity. The purpose of this program is to increase understanding of the use of mangrove flowers and leaf litter to be used as functional drinks, and understanding and skills on how to make good raw materials for flowers or mangrove leaves to be used as BPOM standardized functional drinks. The final goal is the empowerment of PKK women in Palaes Village to manage mangrove plants into functional drinks that will be traded in the future at Palaes Tourism Village. The specific target and objective of this activity is the process of making good simplicia with the introduction of the drying process and the BPOM standard and the form of natural tea products in the following year that are ready to use which are marketed online or on the website. The implementation methods that will be applied to this program are counseling, training, mentoring and evaluation of aspects that increase the ability of PKK mothers to earn additional income and achieve cleanliness and beauty problems. The output of this program includes dry simplicia whose quality is known. and leaning that is ready to be implemented in 2024.